2012
DOI: 10.1111/all.12074
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of the SQ‐standardized grass allergy immunotherapy tablet in mono‐ and polysensitized subjects

Abstract: The efficacy of single-allergen-specific immunotherapy in polysensitized subjects is a matter of debate. We therefore performed a post hoc analysis of pooled data from six randomized, double-blind, placebo-controlled trials (N = 1871) comparing the efficacy and safety of the SQ-standardized grass allergy immunotherapy tablet (AIT), Grazax (Phleum pratense 75 000 SQ-T/2800 BAU, ALK, Denmark), in mono- and polysensitized subjects. A statistically significant reduction in the mean total combined symptom/medicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(47 citation statements)
references
References 15 publications
2
39
0
6
Order By: Relevance
“…This is consistent with a recent pooled post hoc analysis including several studies on the SQ grass SLIT-tablet, suggesting that the observed effects were not dependent on sensitization status. 35 The presence of clinical symptoms to another perennial allergen to which the subject is regularly exposed was an exclusion criterion because other indoor sensitizations might interfere during efficacy assessment periods.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with a recent pooled post hoc analysis including several studies on the SQ grass SLIT-tablet, suggesting that the observed effects were not dependent on sensitization status. 35 The presence of clinical symptoms to another perennial allergen to which the subject is regularly exposed was an exclusion criterion because other indoor sensitizations might interfere during efficacy assessment periods.…”
Section: Discussionmentioning
confidence: 99%
“…148 Consequently, consideration needs to be given as to whether patients are (i) clinically monoallergic (where only 1 allergen is driving symptoms) and polysensitized or (ii) poly-allergic (symptoms with overlapping exposure to multiple different allergens) and polysensitized. Immunotherapy with a single allergen extract is effective in the first, 149 while immunotherapy has been shown to be ineffective 150 or less effective in the last situation. 151 This may be apparent from the history or may need investigation with component-resolved diagnostics or assessment with nasal or conjunctival provocation challenges where the clinician is experienced in these diagnostic procedures.…”
Section: Polysensitized Patientsmentioning
confidence: 99%
“…Pooled data from six randomized, double-blind, placebo controlled trials was used to compare the efficacy and safety of treatment with timothy SLIT tablets in mono-and polysensitized subjects [50]. Eighty percent of subjects in the studies were polysensitized.…”
Section: Drug Profilementioning
confidence: 99%